2016
DOI: 10.1007/s00787-016-0904-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations of attention-deficit/hyperactivity and other childhood disorders with psychotic experiences and disorders in adolescence

Abstract: Prodromal symptoms of psychosis are associated with an increased risk of transition, functional impairment, poor mental health, and unfavorable developmental prospects. Existing interventions targeting the prodrome are non-satisfactory. It may thus be more promising to attempt to identify risk factors in the premorbid phase preceding the prodrome to increase the chances of successful preventive approaches. Here, we investigate whether childhood mental disorders in general and attention-deficit/hyperactivity di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 64 publications
3
28
1
Order By: Relevance
“…Importantly, psychotic‐like experiences were also associated with emotional and behavioural difficulties earlier in childhood, including anxiety, depression, aggressive behaviour and autistic traits, at ages 3 and 6 years. This is in line with studies demonstrating that autistic symptoms, attention‐deficit/hyperactivity disorder and other DSM‐based psychiatric disorders are predictive of adolescent psychotic‐like experiences . Moreover, population‐based studies have shown that genetic vulnerability to schizophrenia also confers antecedent risk of emotional and behavioural difficulties in childhood .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Importantly, psychotic‐like experiences were also associated with emotional and behavioural difficulties earlier in childhood, including anxiety, depression, aggressive behaviour and autistic traits, at ages 3 and 6 years. This is in line with studies demonstrating that autistic symptoms, attention‐deficit/hyperactivity disorder and other DSM‐based psychiatric disorders are predictive of adolescent psychotic‐like experiences . Moreover, population‐based studies have shown that genetic vulnerability to schizophrenia also confers antecedent risk of emotional and behavioural difficulties in childhood .…”
Section: Discussionsupporting
confidence: 87%
“…Importantly, the interpretation that internalising problems mediated the associations to subsequent psychotic‐like experiences is also compatible with our data. In addition, our findings extend earlier studies that suggested a direct association between symptoms attention‐deficit/hyperactivity disorder, autism spectrum disorder, aggressive behaviour and subsequent psychotic‐like experiences . The predictive value of emotional problems might reflect a general vulnerability to overlapping networks of affective and emotional psychopathology across development, of which psychotic‐like experiences might be a common manifestation in pre‐adolescence .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, schizophrenia patients or high-risk individuals with ADHD perform worse in neuropsychological tests, when compared to those without ADHD ( Keshavan et al, 2003 ; Oner and Munir, 2005 ; Donev et al, 2011 ). Of relevance for this work, diagnosis of ADHD in peri-adolescence is associated with the emergence of schizophrenia symptomatology later in life ( Kim-Cohen et al, 2003 ; Hennig et al, 2017 ). In this scenario, our data may also indicate that CBD displays a preventive potential for high-risk individuals with ADHD as a comorbidity or for those that develop schizophrenia and display a previous history of ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…ADHD patients had a higher risk of psychotic experiences at age 12 (OR: 1.70, 95% CI: 1.28-2.27) and of psychotic disorders at age 18 (OR: 2.31, 95% CI: 1.03-5.15). Especially the ADHD combined subtype at age 7 was strongly associated with psychotic experiences at age 12 (OR: 3.26, 95% CI: 1.74-6.10) [11].…”
Section: Introductionmentioning
confidence: 99%